Stereotipe Teroris dan Terduga Teroris di Lingkungan Masyarakat - Siti Kholifah (Islamic Insights Journal, 2022)
The incident of terror bombings in May 2018 in Surabaya and Sidoarjo, as well as the arrest of several suspected terrorists in Sidoarjo, Malang and Probolinggo caused many responses among the public as well as political elites and religious leaders. Criticism of this terrorist act came from various society, but there are also those who consider this terrorist act as a manipulation. For this reason, this study focused on the stereotype of terrorist and suspected terrorist provided by the people who live around them. This research was conducted in Surabaya, Sidoarjo, Malang and Probolinggo which were areas where acts of terror and arrests of suspected terrorist have occurred. This research was qualitative research with a case study approach, and used the concept of stereotypes as a tool analysis. The data collection were carried out through observation, documentation and in-depth interview with informants who selected by purposive. The data analysis used pattern analysis. This study asserted that people in housing complexes tend to stereotype terrorist and suspected terrorist as people who behave ‘ordinary’ as people in general, even though they rarely interact and keep their distance from other people. Meanwhile, people living in villages and flats provided stereotype to terrorist and suspected terrorist as closed and strange people, although some of them also take part in activities in the villages or flats. This situation occurs because the characteristics of the housing complexes are more individualistic and social control is lower than the community in the villages or flats whose interaction more intensity with higher social control. Keywords: terrorist, suspected terrorist, stereotype.